Opinions on the current pandemic of COVID-19: Use functional food to boost our immune functions - Bo Han; Ba X. Hoang (Elsevier, 2020)
The pandemic of novel coronavirus caused COVID-19 had resulted in a high number of hospitalizations and deaths and caused a devastating toll on human and society health. The symptoms of the infected patients vary significantly, from life-threatening to mild or even asymptomatic. This clinical observation led to hypothesize on the critical role of host innate immunity in the disease development and progression. As the first defense barrier against microorganisms, the innate immune reaction determines not only the viral infection rate but also immune-mediated response. Therefore, promote healthy behaviors to enhance innate immunity with functional food and nutritional agents may be a rational strategy for minimizing damages caused by viruses to global health.